Photodynamic antimicrobial chemotherapy activities of porphyrin- and phthalocyanine-platinum nanoparticle conjugates - Managa, Muthumuni Elizabeth (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
This work reports on the conjugation of differently shaped Pt nanoparticles (PtNPs) with ClGa(III) 5,10,15,20-tetrakis-(4-carboxyphenyl) porphyrin (1) as well as chloro - (5,10,15,20-tetrakis (4- (4- carboxy phenycarbonoimidoyl) phenyl) porphyrinato) gallium(III) (2) The work also reports on platination of dihydroxosilicon octacarboxyphthalocyanine (OH)₂SiOCPc (3) to give dihydroxosilicontris(diaquaplatinum)octacarboxyphthalocyanine (OH)₂SiOCPc(Pt)₃ (4). The resulting conjugates were used for photodynamic antimicrobial chemotherapy against S. aureus, E. coli and C. albicans. The degree of photo-inactivation is dependent on concentration of the conjugates, light dose (fluence) and illumination time. The log reduction obtained for 1 when conjugated to cubic PtNPs was 4.64 log (which indicate 99.99 percent of the bacteria have been killed), which is much higher than 3.94 log unit for 1-hexagonal PtNPs and 3.31 log units for 1-unshaped PtNPs. Complex 2 conjugated to hexagonal PtNPs showed 18 nm red shift in the Soret band when compared to 2 alone. Complex 2 and 2-hexagonal PtNPs as well showed promising photodynamic antimicrobial chemotherapy (PACT) activity against S. aureus, E. coli and C. albicans in solution where the log reduction obtained was 4.92, 3.76, and 3.95 respectively for 2-hexagonal PtNPs. The singlet oxygen quantum yields obtained were higher at 0.56 for 2-hexagonl PtNPs in DMF while that of 2 was 0.52 in the same solvent. This resulted in improved PACT activity for 2-hexagonal PtNPs compared to 2. Complex 4 showed slight blue shifting of the absorption spectrum when compared to complex 3 The antimicrobial activity of 4 were promising as the highest log reduction value was observed when compared to the porphyrin conjugates.
Keywords: Photochemotherapy; Anti-infective agents; Porphyrins; Phthalocyanines; Platinum; Nanoparticles; Bioconjugates; Electrospinning